Assessment and Documentation of Sexual Health Issues of Recent Combat Veterans Seeking VHA Care. (19th February 2013) - Helmer, Drew A.; Beaulieu, Gregory R.; Houlette, Cheryl; Latini, David; Goltz, Heather H.; Etienne, Samuel; Kauth, Michael
Abstract Introduction Sexual health is an important aspect of human existence associated with disease and overall health. Despite these associations and the existence of medical treatments to improve sexual function, sexual health is often overlooked in health care. Recent combat veterans may be particularly vulnerable to sexual health issues due to their deployment‐related health issues such as mental health conditions, prescription medications use, and psychosocial challenges. Aim This study assesses the sexual health issues of recent combat veterans seeking care at a Veterans Affairs Medical Center (VAMC) documented in the primary care and mental health notes from the first 6 months of care. Main Outcome Measures Documentation of sexual health issues in the progress notes (coded into categories), primary care vs. mental health care visit note, initial vs. follow‐up visit notes, and templated vs. non‐templated text. Methods This is a retrospective chart review of the first 158 consecutive patients seen for an initial assessment in the VAMC post‐deployment clinic. Medical records were reviewed and text of sexual health issues and relevant patient and care characteristics were abstracted and coded into variables. Results Almost 25% of patients had documented sexual health issues in the first 6 months of care. We coded 52 separate sexual health issues into 13 distinct categories. Overall, most sexual health issues were documented in mental health care notes, in non‐templated text, and at follow‐up visits. The use of templated text appeared to drive the documentation of low libido (the most common sexual health issue) in mental health care notes. Conclusions Sexual health issues are prevalent in recent combat veterans seeking care at a VAMC, but patterns of documentation suggest that they may be under‐reported or incompletely addressed. A more systematic and provider‐initiated approach to assessment of sexual health may promote fuller discussion of sexual health issues and optimize management.